Health-Related Quality of Life and Perceived Stigma in Eosinophilic Esophagitis: A Real-World, US, Web-Based Survey - Benjamin D. Gold; Bridgett Goodwin; Kimberly Davis; Carolyn Sweeney; Maria Reynolds; Jeanne Jiang; Tao Fan; Mena Boules; Szu-Ta Chen; David A. Katzka (Gastro Hep Advances)
Background and Aims: Eosinophilic esophagitis (EoE) is associated with impaired health-related quality of life (HRQoL) and stigma perceptions. Therefore, we examined the real-world impact of EoE on the daily life and ability to function in adolescents (caregiver-reported) and adults with EoE in the United States of America in a noninterventional, cross-sectional, web-based survey. Methods: HRQoL was assessed using the Short Form Health Survey (domains: vitality and social functioning) and the European Health Interview Survey (domain: sleep). Scores for the survey responses were on a scale of 0 to 100; higher scores indicated better performance in the HRQoL domain. Anxiety and depression were assessed using the Patient-Reported Outcomes Measurement Information System (PROMIS) short forms. Higher PROMIS scores indicated higher levels of anxiety and depression; a mean score of 50.0 was representative of the general population (individuals without EoE). The sources and impact of EoE-associated perceived stigma were also examined. Results: Overall, 211 caregivers and 184 adults completed the survey. HRQoL scores were slightly higher for adolescents than adults with EoE (adolescent and adult scores, respectively: vitality, 50.3 and 36.1; social functioning, 64.0 and 62.4; and sleep, 55.7 and 52.0). Anxiety scores (adolescent and adult scores, respectively: 54.8 and 59.7) and depression scores (54.5 and 56.3) were higher in those with EoE than in the general population. Most participants reported experiencing perceived stigma, which was most commonly from family, friends, classmates, or health-care professionals. Conclusion: Patients with EoE had poor HRQoL, which was demonstrated by the high EoE-associated emotional and psychological burdens and perceived stigma they experience.